Understanding the yeast host cell response to recombinant membrane protein production. (20th May 2011) - Bawa, Zharain; Bland, Charlotte E.; Bonander, Nicklas; Bora, Nagamani; Cartwright, Stephanie P.; Clare, Michelle; Conner, Matthew T.; Darby, Richard A.J.; Dilworth, Marvin V.; Holmes, William J.; Jamshad, Mohammed; Routledge, Sarah J.; et al.
Abstract : Membrane proteins are drug targets for a wide range of diseases. Having access to appropriate samples for further research underpins the pharmaceutical industry's strategy for developing new drugs. This is typically achieved by synthesizing a protein of interest in host cells that can be cultured on a large scale, allowing the isolation of the pure protein in quantities much higher than those found in the protein's native source. Yeast is a popular host as it is a eukaryote with similar synthetic machinery to that of the native human source cells of many proteins of interest, while also being quick, easy and cheap to grow and process. Even in these cells, the production of human membrane proteins can be plagued by low functional yields; we wish to understand why. We have identified molecular mechanisms and culture parameters underpinning high yields and have consolidated our findings to engineer improved yeast host strains. By relieving the bottlenecks to recombinant membrane protein production in yeast, we aim to contribute to the drug discovery pipeline, while providing insight into translational processes.